2020
DOI: 10.1002/dvdy.213
|View full text |Cite
|
Sign up to set email alerts
|

GFP expression pattern in pituitary and gonads under the control of nuclear progesterone receptor promoter in transgenic zebrafish

Abstract: Background: The nuclear progesterone receptor (Pgr) is a ligand-dependent transcription factor primarily responsible for mediating progesterone actions relevant for reproduction across vertebrates. Information on the cellular localization of Pgr expression in the reproductive system is required for developing a comprehensive approach to elucidate the role of Pgr in reproduction. Results: We generated transgenic zebrafish Tg(pgr:eGFP) that express enhanced green fluorescent protein (eGFP) driven by promoter seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
(104 reference statements)
0
2
0
Order By: Relevance
“…Progesterone plays critical roles in reproduction across vertebrates. Nuclear PGR is a ligand-dependent transcription factor responsible for mediating progesterone action related to reproduction [ 72 ]. Our results indicated that closed DARs related to the transcriptional activity of NRs, which sense change among androgen, glucocorticoid, and progesterone in the pituitary.…”
Section: Discussionmentioning
confidence: 99%
“…Progesterone plays critical roles in reproduction across vertebrates. Nuclear PGR is a ligand-dependent transcription factor responsible for mediating progesterone action related to reproduction [ 72 ]. Our results indicated that closed DARs related to the transcriptional activity of NRs, which sense change among androgen, glucocorticoid, and progesterone in the pituitary.…”
Section: Discussionmentioning
confidence: 99%
“…As a female sex hormone mainly regulates gonadal development, little is known regarding the direct regulation of progesterone on gonadotrophs in male fish. The only evidence is the expression of the re- ceptor in the pituitary of zebrafish [105], and that pgr knockout in tilapia males causes a decrease in gonadal size and fshβ expression in the pituitary [106]. In dispersed cells from pituitaries of female tilapia, higher doses of 17α,20β-dihydroxy-4-pregnen-3-one (DHP) increased the expression of GnRH receptors, dopamine receptors (DRD2), and gonadotrophins in a dose-dependent manner [96].…”
Section: Aromatase Interaction With Sex Steroids In the Gonadotrophs ...mentioning
confidence: 99%